Maternal resilience and parental adjustment to disability in mothers of Special Basic Educational Centers of Lima este - Tumbaco Choez, Liliana (2019)
Objetives: The present research had as main object to determine the significant relationship betweenmaternal resilience and parental adjustment to the disability in mothers of special primary school inEast Lima, 2016. Materials and Methods: The study is of non-experimental, cross-sectional andcorrelation, there were 98 mothers whose ages ranged between 20 and 59 years old who had childrenwith different disabilities, the instruments used were The Maternal Resilience Scale designed by Roque,Acle y García (2009) and the Questionnaire of parental attitude towards the disability by Fernández,Oliva y Calderón (2013). Results: The results showed that between maternal resilience and parentaladjustment to the disability there is a significant association (x2= 16.267, p ˂ 0.05). Conclusions: Thatis, mothers with high levels of maternal resilience present greater adaptation to adversity, and 2% ofmothers who are in the shock phase have low levels of resilience.